Tax Cryptographia: Exploring the Fiscal Design of Cryptocurrencies - Christians, Allison (McGill Law Journal / Revue de droit de McGill, 2019)
While the founders of cryptocurrencies may not conceptualize their efforts as such, the infrastructural choices they make in designing their systems mimic those routinely made by lawmakers in the design of fiscal policy. The totality of their decision-making in this regard constitutes essential elements of “taxation” written into the governance structure of the cryptocurrency system — its tax cryptographia. This article examines how cryptocurrency founders determine what common goods are necessary to make their systems viable and then design a way to fund them. The object of comparing certain cryptographic design elements to taxation is to examine how investors, speculators, enthusiasts, and skeptics should assess the decisions that founders make, and why it might matter if the participants in cryptocurrency systems recognize the fiscal infrastructure as a reproduction of state-like functions that serve to allocate the cost and benefits of participating in the collective activity despite the core motivation of cryptocurrency to bypass centralized and hierarchical political institutions.